Development of Student Worksheets Assisted by Canva in Science Learning for Grade V Students - Ariza, Vanny Selly; Frima, Aren; Raflesia, Citra (Global Education Journal, 2025)
Social studies education has an important function in developing insight and shaping students' character so they are able to adapt to social changes that occur around them. This study aims to produce a valid, practical and effective LKPD design in learning. This research method is development research using the ADDIE development model. The research subjects were fifth grade students of SD Negeri 28 Lubuklinggau. Data collection techniques were interviews, questionnaires and learning outcome tests. Data analysis techniques were validation results analysis, practicality and effectiveness analysis of LKPD results. The results showed that based on the results of the validation questionnaire conducted by three LKPD experts assisted by Canva, it was categorized as very valid with a percentage of 95% from language experts, 87% from media experts and 92% from material experts. The overall results of the practicality test from the student response questionnaire (One to One Test and Small Group Test) and the teacher response questionnaire were categorized as very practical with a percentage of 91%. And the effectiveness test from the pretest and posttest results using the N-gain formula obtained a value of 0.63 with a moderate category. Based on the research data obtained, it can be concluded that the Student Worksheet (LKPD) assisted by Canva in science learning is declared valid, practical and effective for use in the learning process.